Phosphorus intensity determines short-term P uptake by pigeon pea (Cajanus cajan L.) grown in soils with differing P buffering capacity : Comparison of E- and L-values - Pypers, Pieter; Delrue, J; Diels, J.; Smolders, E.; Merckx, Roel (Springer, 2006)
Phosphorus (P) uptake by plant roots depends on P intensity (I) and P quantity (Q) in the soil. The relative importance of Q and I on P uptake is unknown for soils with large P sorption capacities because of difficulties in determining trace levels of P in the soil solution. We applied a new isotope based method to detect low P concentrations (<20 µg P l?1). The Q factor was determined by assessment of the isotopically exchangeable P in the soil (E-value) and the I factor was determined by measurement of the P concentration in the pore water. A pot trial was set up using four soils with similar labile P quantities but contrasting P buffering capacities. Soils were amended with KH2PO4 at various rates and pigeon pea (Cajanus cajan L.) was grown for 25 days. The P intensity ranged between 0.0008 and 50 mg P l?1 and the P quantity ranged between 10 and 500 mg P kg?1. Shoot dry matter (DM) yield and P uptake significantly increased with increasing P application rates in all soils. Shoot DM yield and P uptake, relative to the maximal yield or P uptake, were better correlated with the P concentration in the pore water (R 2 = 0.83 0.90) than with the E-value (R 2=0.40 0.53). The observed P uptakes were strongly correlated to values simulated using a mechanistic rhizosphere model (NST 3.0). A sensitivity analysis reveals that the effect of P intensity on the short-term P uptake by pigeon pea exceeded the effect of P quantity both at low and high P levels. However, DM yield and P uptake at a given P intensity consistently increased with increasing P buffering capacity (PBC). The experimental data showed that the intensity yielding 80% of the maximal P uptake was 4 times larger in the soil with the smallest PBC compared to the soil with the largest PBC. This study confirms that short-term P uptake by legumes is principally controlled by the P intensity in the soil, but is to a large extent also affected by the PBC of the soil.